Long-COVID is Associated with Impaired Red Blood Cell Function - Kronstein-Wiedemann, Romy; Tausche, Kristin; Kolditz, Martin; Teichert, Madeleine; Thiel, Jessica; Koschel, Dirk; Tonn, Torsten; Künzel, Stephan R. (Hormone and Metabolic Research, 2023)
COVID-19 disease, caused by the severe acute respiratory syndrome virus 2 (SARS-CoV-2), induces a broad spectrum of clinical symptoms ranging from asymptomatic cases to fatal outcomes. About 10–35% of all COVID-19 patients, even those with mild COVID-19 symptoms, continue to show symptoms, i. e., fatigue, shortness of breath, cough, and cognitive dysfunction, after initial recovery. Previously, we and others identified red blood cell precursors as a direct target of SARS-CoV-2 and suggested that SARS-CoV-2 induces dysregulation in hemoglobin- and iron-metabolism contributing to the severe systemic course of COVID-19. Here, we put particular emphasis on differences in parameters of clinical blood gas analysis and hematological parameters of more than 20 healthy and Long-COVID patients, respectively. Long-COVID patients showed impaired oxygen binding to hemoglobin with concomitant increase in carbon monoxide binding. Hand in hand with decreased plasma iron concentration and transferrin saturation, mean corpuscular hemoglobin was elevated in Long-COVID patients compared to healthy donors suggesting a potential compensatory mechanism. Although blood pH was within the physiological range in both groups, base excess- and bicarbonate values were significantly lower in Long-COVID patients. Furthermore, Long-COVID patients displayed reduced lymphocyte levels. The clinical relevance of these findings, e. g., as a cause of chronic immunodeficiency, remains to be investigated in future studies. In conclusion, our data suggest impaired erythrocyte functionality in Long-COVID patients, leading to diminished oxygen supply. This in turn could be an explanation for the CFS, dyspnea and anemia. Further investigations are necessary to identify the underlying pathomechanisms.
Keywords: long-COVID; oxygen binding; COHb